Jihad dan Anti Kafir dalam Geger Cilegon 1888 - Ahmad Maftuh Sujana; Saeful Iskandar (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2019)
Colonial exploitation that occurred in the 19th century in the archipelago. Creating conditions that can encourage people to carry out social movements that are dominated by continuous economic, political and cultural conditions and have led to the disorganization of traditional societies and their institutions. The entry of the Dutch in the 19th century began to cause enormous problems for the people of Banten, because the changes made by the Dutch government changed the system of government created by the Sultanate of Banten. From the traditional government structure switched to the Modern (European) government system. This has a negative impact on the structure of people's lives. Banten Ulama with the spirit of jihad, the spirit of anti-Islam, sometimes even the spirit of Nativism and Revivalism, became the driving force for various social movements that flourished in the 19th century. Throughout the 19th and early 20th centuries this movement was a historical symptom of the indigenous peasant society. Almost all of these social movements occur due to high tax collections and heavy work that puts pressure on farmers. So that in this case, the kiai's leadership in carrying out the movement against the invaders is all based on the same motivation and conditions, namely maintaining aqidah and worship. Against munkar, polytheism and kufr which are carried out in the framework of munkar ma'ruf nahyi deeds. Everything is based on sincerity to fortify Islam from the influence that damages Islamic aqidah, worship and mu'amalah. This is clearly manifested in the history of struggle which was marked by Ulama throughout the archipelago